Molecular analysis of eight splicing variants in the hydroxymethylbilane synthase gene - Ren, Yi; Wang, Jiajia; Li, Shuang; Lei, Jiajia; Liu, Yunfeng; Wang, Yan; Gao, Fei; Wang, Jianhong; Yin, Jianhong; Yang, Jing (Frontiers in Genetics, 2023)
Background: Molecular genetic testing is the most sensitive and specific method to confirm acute intermittent porphyria (AIP), a rare autosomal dominant disease, caused by Hydroxymethylbilane synthase (HMBS) gene mutation. According to the Human Gene Mutation Database (HGMD), approximately 20% of the reported HMBS gene variants affect pre-RNA splicing. Thus, the ensuing challenge is how to decipher the pathogenicity of these splicing variants. Methods: Using next-generation sequencing, we identified a novel heterozygous variant in the HMBS gene (c.160 + 5G>C) from a Chinese family with AIP. And, previously, seven HMBS variants (c.33 + 5G>A, c.88-16_88-4del, c.88-2A>G, c.161-1G>C, c.652-1G>A, c.772-2A>G and c.772-1G>C) have been reported to be linked with AIP. Herein, we performed a valid and novel in vitro minigene assay to analyze the pathogenicity of these eight splicing variants. Results: By minigene assay in 293 T cell experiments, we demonstrated that all eight variants caused splicing defects in the pre-mRNA of the HMBS gene: c.160 + 5G>C (intron3p_141bp retention), c.33 + 5G>C(intron1p_91bp retention), c.88-16_88-4del and c.88-2A>G (Exon3p_15bp deletion), c.161-1G>C (Exon4p_18bp deletion), c.652-1G>A (Exon11p_1bp deletion), c.772-2A>G and c.772-1G>C (intron11q_104bp retention or Exon12p_4bp deletion).Encouragingly, the c.160 + 5G>C RNA sequencing from peripheral blood lymphocytes was consistent with the minigene assay result. Conclusion: We have made a pioneering attempt to apply minigene in vitro validation to the HMBS gene to evaluate the splicing effect of eight variants, including a novel splice variant (c.160 + 5G>C). This study provides a molecular basis for future research on the pathogenesis and gene therapy of AIP.